Kapasitas Sababay Winery Tour Sebagai Daya Tarik Wisata Buatan Unggul Di Desa Medahan, Gianyar, Bali - Treacynthia, Agatha; Sanjiwani, Putri Kusuma (JURNAL DESTINASI PARIWISATA; Vol 9 No 1 (2021): VOL 9, NO 1 (2021): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATA, 2021)
Sababay Winery is a lokal wine company that has wine tourism which focus on winery tour. The purpose of this research is to find out about winery tour activities and its capability as a superior, artificial tourist attractions in Medahan village. The research methods are using qualitative method with primary dan secondary data types. The methods of collecting data are through interviews, observations and documentations. The methods of determination of informants are purposive sampling. The result of this research, Sababay Winery tour is a tour that explain about how to make wine directly also trying some wine that Sababay Winery has and in the capacity of winery tour as superior artificial tourist attractions. This research explains about how to make wine instantly from its factory, along with ‘wine testing’ which the company has. Explaining privileges and superiority of wines made by Sababay Winery so that they are able to become other lokal wine competitors in Bali. The Sababay Wine Factory empowers human resources from the village of Medahan to become a reliable and trained workforce for the welfare of the lokal community. Sababay Winery is trying its best in helping development of Medahan village by holding CSR activities for Medahan village. Keyword: Sababay Winery tour, Wine Tourism, Artificial Tourist Attraction